The Principal's Strategy for Strengthening National Identity in Globalization Era - Sarmini Sarmini; Agus Suprijono; Indri Fogar Susilowati; Charis Achmadi; Agung Dwi Bahtiar El Rizaq (IJORER : International Journal of Recent Educational Research, 2023)
National identity is interesting to be discussed, considering the loss of national boundaries since technological advances increasingly affect daily life. National identity is essential to be implemented from an early age, primarily through the role of education. The focus of this study is to reveal the Principal's strategy for strengthening national identities. This study was conducted using a quantitative approach through a survey of 50 elementary school principals spread over 18 subdistricts in the Sidoarjo Regency. Two things can be concluded from this study. First, national identity is essential for the young generation of mid-globalization. This study shows that every respondent realizes the importance of principal secondary schools developing straightforward policy programs about internalizing national identity. Those policy programs must integrate extracurricular activities, extracurricular activities, building school culture, and various participation activities. Second, most of the respondents agree that their schools have no clear policy as their guidance in internalizing national identity values in learning. Several teachers have integrated national identity values into learning through lesson plans or learning activities. This study recommends developing an applicable policy model to strengthen the national identity of the young generation.